Efektivitas Seng (Zn) sebagai Imunostimulan dalam Produksi Reactive Oxygen Intermediate pada Mencit Balb/C yang Diinfeksi Salmonella typhimurium - Ari Yuniastuti; Nugrahaningsih W H; Zunikhah Zunikhah (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2010)
This study aims to prove the effectiveness of zinc as a micronutrient to increaseimmunostimulatory Reactive Oxygen Intermediate (ROI) production in balb/c miceinfected by Salmonella typhimurium. Research was designed using randomized thePost Test Only Control Group Design. The sample of 24 male mice balb/c are groupedinto four groups, i.e. one control group and three treatment groups (treatment dose of 78ppm/day; 169 ppm/day and 260 ppm/day) intraperitoneally for 14 days with each groupconsisting of six rats. The independent variable is the provision of zinc with various doses,dependent variable is the ROI production of macrophages, which are checked by usingNitroblue Tetrazolium (NBT) Reduction Assay, and control variables are body weight,gender and age. All mice infected with Salmonella typhimurium 105 intraperitoneally onday 8th. At the end of treatment mice were killed and was examined for levels of ROI.Inspection results were analyzed by Kruskal Wallis test. Result showed that doses ofzinc of 78 ppm/day have immunostimulatory effective as the highest ROI productionof mice Balb/c infected with Salmonella typhimurium.Keywords: immunostimulant, Reactive Oxygen Intermediate, zinc (Zn)